Real-time energy management for electric arc furnace operation. (February 2019) - Shyamal, Smriti; Swartz, Christopher L.E.
Highlights: Novel application of NMPC and MHE to electric arc furnace operation using a first principles model. Energy consumption efficiently managed through economic objective function. New initialization scheme proposed for MHE and NMPC that significantly reduces solve time. Case studies demonstrate the economic benefit under real-time dispatch market conditions. Electricity demand peak reduced when changing electricity price profile is used. Abstract: Electric arc furnaces are used extensively in the steel industry for steel production. Development of energy savings strategies for the highly energy-intensive batch process is extremely challenging due to the complexity of the process and lack of measurements due to the harsh operating conditions. Here we introduce a new energy management approach that effectively curtails the energy cost in real-time through the implementation of economically optimal operating decisions. An economics- oriented shrinking horizon nonlinear model predictive control (NMPC) algorithm that exploits time-varying electricity prices is coupled with a multi-rate moving horizon estimator (MHE) to form an integrated decision- making framework. With a detailed first-principles dynamic model functioning at the core, the multi-variable interactions and plant variations are successfully incorporated into the control strategy to achieve reliable performance. We also present a novel initialization scheme for obtaining fast on-line solutions of the economic NMPC and multi-rate MHE dynamic optimization problems. Using this initialization algorithm, we show that the optimal input decisions are obtained with sufficient computational speed for real-time implementation. The energy usage optimization results indicate a significant reduction in the operating cost and peak electricity demand compared to the case where the electricity price profile is not updated.